2022
DOI: 10.1111/ina.13073
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of the effect of current mood states on the thermal sensation in educational buildings

Abstract: Adaptive thermal comfort is a model which considers behavioral and psychological adjustments apart from Fanger's Predicted Mean Vote (PMV)/Percentage of Dissatisfied (PPD) method. In the literature, the differences between the PMV/PPD method and adaptive thermal comfort were mainly considered in aspects of behavioral adjustments in an environment. Conversely, limited studies related to psychological adjustments were considered in detail for thermal comfort. This study purposes to investigate the effects of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This supports the results found by Ibrahim 29 that the negative feeling (‘anger’ in his case) could strengthen the warm feeling. Besides, the impact of ‘depression’ on thermal sensation was reported by Özbey et al 33 They revealed that depression could cause a difference in TSV as large as 0.3, which is similar to the finding of the current study that the average TSV of students who felt upset was 0.4 higher than the TSV of other students. According to psychosomatic studies, these negative moods could cause an increase in heart rate and metabolic rate, 60,61 which could further increase subjects’ TSV.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This supports the results found by Ibrahim 29 that the negative feeling (‘anger’ in his case) could strengthen the warm feeling. Besides, the impact of ‘depression’ on thermal sensation was reported by Özbey et al 33 They revealed that depression could cause a difference in TSV as large as 0.3, which is similar to the finding of the current study that the average TSV of students who felt upset was 0.4 higher than the TSV of other students. According to psychosomatic studies, these negative moods could cause an increase in heart rate and metabolic rate, 60,61 which could further increase subjects’ TSV.…”
Section: Discussionsupporting
confidence: 91%
“…Yet, there have been very few studies on thermal sensation that considered mood states. According to the limited existing studies, [29][30][31][32][33][34] the impact of mood states on thermal sensation could be strong and hence should be considered together with other factors in TSV-related studies, as suggested in Figure 1. 29,32 Given the above-mentioned research gaps, this study aimed to investigate students' thermal sensation in a library indoor environment setting, considering environmental factors, personal factors and mood states at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, limited research was conducted to investigate the significance of the psychological adjustments. [10,14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, shortened POMS surveys such as POMS -2Y (for young participants) [26] and POMS -2A (for adults) [28] exist in the literature as well. Full version of the POMS questionnaire can be seen in [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation